DEMENTIA WITH LEWY BODIES: CLINICAL AND PHARMACOLOGICAL MANAGEMENT STRATEGIES (International Seven Journal of Multidisciplinary, 2025)
Dementia with Lewy bodies (DLB) is a progressive neurodegenerative disease characterized by the pathological accumulation of α-synuclein in the central nervous system and represents the second most prevalent cause of neurodegenerative dementia after Alzheimer’s disease (GALVIN, 2024; PRASAD et al., 2023). Clinically, it is manifested by cognitive fluctuations, recurrent visual hallucinations, spontaneous parkinsonism, and a high prevalence of sleep disorders, in addition to marked sensitivity to neuroleptics (WALKER; ZACCAI; QIZILBASH, 2015; ELDER et al., 2022). This study aimed to review the current evidence on the clinical and pharmacological management of DLB. This is a narrative literature review based on articles indexed in the PubMed database. The findings indicate that diagnosis is predominantly clinical, supported by biomarkers, and that treatment is essentially symptomatic, with emphasis on acetylcholinesterase inhibitors and multidisciplinary non-pharmacological interventions, which are fundamental to reducing iatrogenesis and improving quality of life (ALTY; LARNER, 2020; PARMERA et al., 2022).